2005
DOI: 10.1002/jbt.20063
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of adjacent E‐box and nuclear factor 1‐like DNA binding sequence in the human CYP1A2 promoter

Abstract: To better understand the molecular mechanisms of cytochrome P450 1A2 (CYP1A2) regulation, we have characterized a region of the promoter (+3 to -176) that contains a single E-box and an adjacent nuclear factor 1 (NF1)-like DNA binding site. The E-box was shown to specifically bind nuclear proteins that were recognized by antibodies against upstream stimulatory factor (USF) 1 and 2. Comparison of NF1 binding proteins in HepG2 cells and primary cultures of rat hepatocytes revealed different patterns of DNA-prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The interplay between HNF1-alpha and USF1/2 has been previously shown to be implicated in the liver-specific expression of the pyruvate kinase gene, in the regulation of three human class I alcohol dehydrogenase genes and in the constitutive expression of CYP1A2 [43-45]. Considering that UGT1A1-mediated glucuronidation is the primary route of irinotecan inactivation, it was suggested that the level of UGT1A1 expression might contribute to the differential chemosensitivity of colon tumors [46-48].…”
Section: Discussionmentioning
confidence: 99%
“…The interplay between HNF1-alpha and USF1/2 has been previously shown to be implicated in the liver-specific expression of the pyruvate kinase gene, in the regulation of three human class I alcohol dehydrogenase genes and in the constitutive expression of CYP1A2 [43-45]. Considering that UGT1A1-mediated glucuronidation is the primary route of irinotecan inactivation, it was suggested that the level of UGT1A1 expression might contribute to the differential chemosensitivity of colon tumors [46-48].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CYP1A2 is mainly hepatic-specific. Several transcription factors have been implicated as regulators of the constitutive and tissue-specific expression of CYP1A2, including members of the nuclear factor 1 family of transcription factors (Narvaez et al, 2005) and the liver-enriched transcription factor HNF1 (Chung and Bresnick, 1997). Moreover, DNA binding sequences of several putative regulatory factors have also been characterized, including activator protein-1 element (Quattrochi et al, 1998) and multiple E-box motifs (Narvaez et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several transcription factors have been implicated as regulators of the constitutive and tissue-specific expression of CYP1A2, including members of the nuclear factor 1 family of transcription factors (Narvaez et al, 2005) and the liver-enriched transcription factor HNF1 (Chung and Bresnick, 1997). Moreover, DNA binding sequences of several putative regulatory factors have also been characterized, including activator protein-1 element (Quattrochi et al, 1998) and multiple E-box motifs (Narvaez et al, 2005). However, the organization of the CYP1A cluster on chromosome 15, in which a common 23.3-kb sequence separates CYP1A1 and CYP1A2, suggests the possibility that distal regulatory elements may be shared (Corchero et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed studies of regulation of transcription have shown that NF1 can function either as an activator or as a repressor [26]. Thus, NF1 affects a broad range of biological activities: a) cell differentiation in embryogenesis [27]; b) regulation of proteins involved in cell-cell (28) and cell-extracellular matrix interactions important in epithelial-mesenchymal transition (EMT) [28]; c) participation in the regulation of environmental stress genes CYP1A1 [29], CYP1A2 [30], CYP2A3 [31]; d) regulation of expression of mitochondrial adenine nucleotide translocator-2 gene (ANT2), indicating the possibility that NF1 might be involved in the regulation of cell energy metabolism [32]; e) cell cycle regulation and growth arrest due to transcription regulation of genes encoding cyclin D [33], GAAD153 [34], p53 [35] and p21 [36].…”
Section: Participation Of Nf1 Proteins In Various Cell Functionsmentioning
confidence: 99%